Cytochromes P450 Metabolic and Toxicological Aspects - Ioannides, Costas;Ed (CRC Press, 1996)
Examines cytochromes P450 proteins and their role in toxicity/carcinogenicity and the metabolism of foreign chemicals. The text, a study of the function of these proteins, presents methods for predicting the pathways and outcome of chemical metabolism.